The Influence of Digital Literacy and Self-Efficacy on The Professional Competency of Unesa Labschool Teachers in The Society 5.0 Era - Guntur Joko Prasetyo; Meini Sondang Sumbawati; Amrozi Khamidi; Mochamad Nursalim (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to analyze the influence of digital literacy and self-efficacy on teacher professional competence, especially in the era of society 5.0. The research sample used was teachers at the Unesa Labschool from elementary, middle and high school levels with a total of 85 people. This type of research uses quantitative with a correlational approach using data analysis techniques through normality tests, linearity tests, classical assumption tests, and hypothesis tests consisting of simple linear regression analysis and multiple linear regression. The research data was processed using the SPSS Statistics program version 27. The results showed that literacy had a significant influence on teacher professional competence by 58.5%, and self-efficacy had a significant influence on teacher professional competence by 67.1%, while literacy digital and self-efficacy together have a significant influence on increasing the professional competence of Unesa Labschool teachers by 70.5%. So the hypothesis is accepted, where digital literacy and self-efficacy have an influence on the level of professional competence of Unesa Labschool teachers in the era of society 5.0.